Diet and Gut Microbiome and the “Chicken or Egg” Problem - Daniel, Hannelore (Frontiers in Nutrition, 2022)
Quantity and quality of the intestinal and fecal microbiome vary considerably between individuals and are dependent on a very large number of intrinsic and environmental factors. Currently only around 15 % of the variance in microbiome diversity can be explained by these factors. Although diet and individual food items have effects, other individual parameters such as gender, age, BMI but also plasma lipids and blood pressure reveal stronger associations with microbiome diversity. In addition, gastrointestinal functions that translate into changes in stool frequency, stool volume and stool appearance rank very high as effectors of microbiome signatures. In particular, the intestinal /colonic transit time is a critical factor that alters the substrate load for bacterial growth and metabolism as it alters simultaneously stool volume, water content, bacterial mass and diversity. And, moreover, metabolic and neurological diseases are frequently associated with marked changes in intestinal transit time that may translate into the reported changes in gut microbiota. This review provides scientific arguments for more comprehensive assessment of the individual´s intestinal phenotype in microbiome studies to resolve the “chicken or egg” problem in these observational studies.